Perceived quality of medical services at outpatient department of public hospitals in Dawro Zone, Southern Ethiopia - Legese Utino; Bezawit Birhanu; Nigusu Getachew; Berhane Megerssa Ereso (BMC Health Services Research, 2023)
Abstract Background Quality of care is fundamental to universal health coverage. Perceived quality of medical services is one of the most determining factors of modern health care service utilization. Between 5.7 and 8.4 million deaths are attributed to poor-quality care each year in low- and middle-income countries (LMICs), and up to 15% of overall deaths are due to poor quality. For instance, in sub-Saharan Africa (SSA), public health facilities lack basic facilities such as a physical environment. Hence, this study aims to assess the perceived quality of medical services and associated factors at outpatient departments of public hospitals in the Dawro zone, Southern Ethiopia. Methods A facility-based cross-sectional study was conducted on the quality of care among outpatient department attendants of Dawro zone public hospitals from May 23 to June 28, 2021. A total of 420 study participants were included via a convenient sampling technique. An exit interview was used to collect data using a pretested and structured questionnaire. Then it was analyzed using the Statistical Package for Social Science (SPSS) version 25. Both bivariable and multivariable linear regressions were carried out. Significant predictors were reported at p < 0.05 with a 95% confidence interval. Result with a 100% response rate. The overall perceived quality was 51.15%. Fifty-six percent of study participants rated perceived quality as poor, 9% as average, and 35% of participants rated it as good perceived quality. The highest mean perception result was related to the tangibility (3.17) domain. Waiting time less than one hour (β = 0.729, p < 0.001), availability of prescribed drugs (β = 0.185, p < 0.003), having information on diagnoses (illness) (β = 0.114, p < 0.047), and privacy maintained (β = 0.529, p < 0.001) were found to be predictors of perceived good quality of care. Conclusion A majority of the study participants rated the perceived quality as poor. Waiting time, availability of prescribed drugs, information on diagnoses (illness), and provision of service with privacy were found to be predictors of client-perceived quality. Tangibility is the predominant and most important domain of client-perceived quality. The regional health bureau and zonal health department should understand the issue and work with hospitals to improve outpatient service quality by providing necessary medication, reducing wait times, and designing job training for health care providers.